Investigation of Knee Flexion Angle Influences on Intra-Body Communication’s (IBC) Signal Attenuation - I W Ibrahim; M M M Aruwa; A.H.A. Razak; A. Ahmad; R. N. Khir (Indonesian Journal of Electrical Engineering and Computer Science, 2018)
Galvanic coupling method is one of the methods introduced in intra-body communication (IBC). IBC uses human body to as the communication medium for data transmission. In this paper, the investigation focuses on signal attenuation performance across knee joint using the galvanic coupling analysis. The signal attenuation was determined by implementing the galvanic coupling analysis at specific knee flexion angle. The galvanic analysis initiated by deciding the operating frequency in between 40 to 60 MHz in order to analyze the signal attenuation between the knee flexion angles. This paper found that the lowest signal attenuation at the operating frequency was 47.25dB, while the highest one was 52.63dB where the knee flexion angle is 0o and 155o respectively. It was concluded that the signal attenuation decrease with the increasing of knee joint existence at the specific flexion angle. However, a wider experiment must be conducted for various data that will correspond to signal attenuation for various influenced human data characteristics.